Cumulative life course and adult socioeconomic status and markers of inflammation in adulthood. Issue 6 (13th May 2008) - Pollitt, R A; Kaufman, J S; Rose, K M; Diez-Roux, A V; Zeng, D; Heiss, G
Abstract : Objective: To examine the association between cumulative life course and adult socioeconomic status (SES) and adult levels of inflammatory risk markers (fibrinogen, white blood cell count (WBC), C-reactive protein (CRP), von Willebrand factor (vWF) and an overall inflammatory score). Design: Retrospective cohort study. Setting: 12 681 white and African-American participants in the Atherosclerosis Risk in Communities (ARIC) study and two ancillary studies. Methods: Participants provided information on SES and place of residence in childhood and young (30–40 years) and mature (45+) adulthood. Residences were linked to census data for neighbourhood SES information. Multiple imputation (MI) was used for missing data. Linear regression and adjusted geometric means were used to estimate the effects of SES on inflammatory risk marker levels. Results: Graded, statistically significant associations were observed between greater cumulative life-course exposure to low education and social class and elevated levels of fibrinogen and WBC among white participants. Stronger graded, statistically significant associations were observed between low adult education, social class and neighbourhood SES and elevated inflammatory levels. Associations were weaker and less consistent in African-Americans. Covariate adjustment attenuated results but many associations remained strong. Conclusions: Our results suggest that cumulative exposure to adverse SES conditions across the life course and low adult SES are associated with an elevated systemic inflammatory burden in adulthood. Chronic systemic inflammation may be one pathway linking low life-course SES and elevated cardiovascular disease risk.